The paschal liturgy in the Philippine context - Laus, Joseph B. ([n.p.] South East Asia Graduate School of Theology, 1977)
One of the most noticeable features of the present liturgical movement is the recovery, restoration, reformation or enrichment of the Paschal liturgy of Holy Week and Easter as the crown of the Christian liturgical year. The paschal liturgy is the heart of the Christian liturgical year. It is the unitive celebration of the one saving act of Christ in which the Church as his mystical body dies and rises again with him. The Paschal liturgy consists of the Rites of Palm Sunday, Maundy Thursday, Good Friday and the Great East Liturgy of the Easter Night.
In partial fulfillment of the requirements for the Degree Master of Theology.
A thesis presented to the South East Asia Graduate School of Theology
Thesis (M. Theo.) - South East Asia